The temporal association between energy drink and alcohol use among adolescents: A short communication. (1st January 2016) - Choi, Hye Jeong; Wolford-Clevenger, Caitlin; Brem, Meagan J.; Elmquist, JoAnna; Stuart, Gregory L.; Pasch, Keryn E.; Temple, Jeff R.
Highlights: We examine the temporal relation between energy drink and alcohol use among youth. Energy drink at baseline is positively related with alcohol use at follow-up. The relation remains while controlling for socio-economic status, previous alcohol use, and impulsivity. Alcohol use prevention efforts should consider energy drinks as risk factors. Abstract: Purpose: To investigate the temporal relation between energy drink and alcohol use among adolescents. Methods: Data were collected from adolescents attending public high schools in two waves ( n  = 894). Results: Path analysis indicated that energy drink use at baseline was positively associated with the number of drinking days but not binge drinking or average drinks per drinking day over the past 30 days at follow-up. This relation remained while controlling for race, age, gender, previous alcohol use, and impulsivity. Conclusions: Alcohol use prevention efforts should consider energy drink use as risk factors for adolescent alcohol use.